Steroid treatment response to post SARS-CoV-2 PANS symptoms: Case series - Berloffa, Stefano; Salvati, Andrea; Pantalone, Gloria; Falcioni, Ludovica; Rizzi, Micaela M.; Naldini, Francesca; Masi, Gabriele; Gagliano, Antonella (Frontiers in Neurology, 2023)
Background Pediatric acute-onset neuropsychiatric syndrome (PANS) is characterized by a wide spectrum of symptoms, including the onset of obsessive-compulsive disorder and/or severely restricted food intake, associated with emotional symptoms, behavioral symptoms, developmental regression, and somatic symptoms. Among the possible triggering agents, infectious agents have been extensively explored. More recently, sporadic case reports describe a possible association between PANS and SARS-CoV-2 infection but data on clinical presentation and treatment are still scarce. Methods We describe a case series (10 children) with acute onset or relapse of PANS symptoms after SARS-CoV-2 infection. Standardized measures (CBCL, CPRS, C-GAS, CGI-S, Y-BOCS, PANSS, and YGTSS) were used to describe the clinical picture. The efficacy of a pulse treatment with steroids for three consecutive months was assessed. Results Our data suggest that the clinical presentation of the COVID-19-triggered PANS is largely similar to that reported in typical PANS, including acute onset, with OCD and/or eating disorders, and associated symptoms. Our data suggest that treatment with corticosteroids may be beneficial for both global clinical severity and global functioning. No serious adverse effects were observed. Both OCD symptoms and tics consistently improved. Among psychiatric symptoms, affective and oppositional symptoms appeared more sensitive to the steroid treatment than the other symptoms. Conclusion Our study confirms that COVID-19 infection in children and adolescents could trigger acute-onset neuropsychiatric symptoms. Thus, in children and adolescents with COVID-19, a specific neuropsychiatric follow-up should be routinely included. Even if a small sample size and a follow-up with only two points (baseline and endpoint, after 8 weeks) limit the conclusions, it seems that steroid treatment in the acute phase may be beneficial and well tolerated.